Clinical outcomes in patients with T4 laryngeal cancer treated with primary radiotherapy versus primary laryngectomy. (1st February 2016) - Vengalil, Salil; Giuliani, Meredith E.; Huang, Shao Hui; McNiven, Andrea; Song, Yuyao; Xu, Wei; Chan, Biu; Hope, Andrew; Cho, John; Bayley, Andrew; Ringash, Jolie; Goldstein, David; et al.
ABSTRACT: Background: The purpose of this study was to determine the clinical outcomes of T4 laryngeal cancers. Methods: T4 laryngeal cancers treated with curative intent from January 2003 to December 2010 were analyzed. Outcomes were evaluated in both primary radiotherapy (+/− chemotherapy) (RT/CRT) and primary surgery cohorts. Results: Among the 65 primary RT/CRT and 42 primary surgery patients included, median follow‐up was 4.4 years. There was a trend for improved locoregional control with surgery (74% vs 88%; p = .08). In the RT/CRT group the 3‐year laryngectomy‐free survival was 67%. The 2‐year gastrostomy dependency rate was 23% with RT/CRT versus 6% with primary surgery ( p = .07). Overall survival (OS) at 3 years was significantly lower in the RT/CRT versus primary surgery group (41% vs 70%; p < .01). Conclusion: Laryngeal preservation is achieved in over two thirds of patients with primary RT/CRT. Patients with low volume minimal cartilage involvement T4 disease may be best suited to RT/CRT. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E2035–E2040, 2016